Prenatal education: profile and expectations of the couples. - Moreira, Rosa Maria Santos (2016)
Characterize the profile and describe the expectations of a sample of couple's participants in prenatal education programs integrated into the 'Tender Adventure - Preparation for childbirth and parenting' ", an outreach project of Nursing School of Coimbra.